Targeted gene panel sequencing of liquid and tissue biopsies reveals actionable genomic alterations in Ghanaian metastatic breast cancer cases - Emmanuella Amoako; Setor Amuzu; Emmanuel Owusu Ofori; Harry Sefoga Akligoh; Randy Tackie; Barikisu Anna Ibrahim; Emmanuel Kofi Quaye; Patrick Kafui Akakpo; Luke Adagrah Aniakwo; Bashiro Jimah; Kofi Ulzen-Appiah; David Hutchful; et al. (Translational Oncology, 2024)
Purpose: Breast cancer is a major cause of cancer-related mortality among African women. The adoption of molecular genomic technologies in the management of cancer cases is limited in Africa. To provide much-needed insights on the feasibility and utility of such precision medicine paradigms in Africa, we conducted a prospective, non-interventional study involving combined tissue and plasma Next-generation sequencing (NGS)-based testing in cancer patients in Ghana. Methods: We recruited 20 newly diagnosed, histologically confirmed, treatment-naïve women with metastatic breast cancer at the Cape Coast Teaching Hospital in Ghana. Tissue (NGS) and cell-free DNA (cfDNA) liquid biopsy analysis were ordered on all 20 patients. Results: All 20/20 (100 %) liquid biopsy samples were acceptable for analysis, whereas only 6/20 (30 %) passed quality control for tissue NGS testing. Liquid biopsy detected 42 cfDNA mutations in 17/20 patients. Of the 17 patients, 3 (17.6 %) had mutations previously associated with African ancestry, including BRCA1 p.K719E, ARAF p.S262I and GATA3 p.G125dup. Eight potentially actionable alterations specific to breast cancer were found in 6/17 (35.3 %) liquid biopsy samples, while potentially actionable mutations non-specific to breast cancer were detected in 12/17 (70.6 %). Tissue biopsy analysis detected mutations in all 6 patients tested, with 3/6 (50 %) patients presenting potentially actionable mutations relevant to breast cancer. Conclusion: Liquid biopsy detected multiple additional actionable variants in Ghanaian women with breast cancer. Plasma cfDNA analysis featured fewer variations in sample preparation which is a key consideration in resource-limited settings. Liquid biopsy presents a great opportunity to improve cancer care in Africa.